Viver e morrer travesti no jornalismo policial: uma análise sobre a desconstrução da identidade trans em Portais Paraibanos - Oliveira, Ana Beatriz Caldas (2018)
The work aims to analyze, based on a Scheduling Theory and the processes of social construction of the news, the symbolic content issued by news portals from Paraíba when dealing with crimes against transvestites, a group of the most vulnerable in the Brazilian criminality spectrum. A survey was structured based on data provided by the LGBT Management of the Secretariat of Women and Human Diversity of the State of Paraíba (SEMDH), referring to homicides of lesbians, gays, bisexuals, transvestites and transsexuals until the year 2016, with which we worked to identify how the local press reported these cases to society. As an object of study, we will analyze as a media event specifically the murders of two transvestites from Paraíba - Inete, who died in 2011 in the city of Campina Grande and Cicarelli, murdered in João Pessoa in 2016-, through news stories published in the state's three largest news portals: Jornal de Paraíba, Portal Correio and G1 Paraíba. The cases were chosen from interviews conducted with LGBT activists and also based on the repercussion in the local press, with a temporal cut that aims to understand the discursive changes that have occurred in relation to these crimes in recent years, arising from the ascendancy of movements organized by and for trans people in Brazil. Through the analysis of the content of the selected cases, we believe that this work can give a brief overview of the situation of tranvestite in Paraíba, their pains and achievements, and what the media are doing for - or against - this population. To broaden the debate, we will briefly discuss the state of public policies for transgender people in the state, in order to reflect on the institutional reasons why these show-deaths follow as events of little relevance.